97.2k views
5 votes
In the following expression, the 2 distributes to the 3 and to the 4 :

(2)(3)(4) = (2)(3)(2)(4)

True or false?

User PLB
by
4.9k points

1 Answer

1 vote
False
If the 2 distributes to the 3 and to the 4, then the expression would be as followed: 2(3+4)
But in this expression, it would be solved as followed:
(2)(3)(4)=
2*3=6*4=24

Hope this helps.
User Cameron Sima
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.